Differential involvement of RalA and RalB in colorectal cancer - Martin, Timothy D. (Landes Bioscience, 2012)
Mutationally activated K-Ras can utilize a multitude of downstream effector proteins to promote oncogenesis. While the Raf and phosphoinositol 3-kinase effector pathways are the best-studied and validated, recent studies have established the critical importance of Ral guanine nucleotide exchange factor (RalGEF) activation of the RalA and RalB small GTPases in cancer biology. Due to recent evidence that the RalGEF-Ral pathway is necessary for the tumorigenic and metastatic potential of KRAS mutant pancreatic ductal adenocarcinoma (PDAC) tumor cells, we investigated whether or not Ral signaling was necessary for KRAS mutant colorectal cancer (CRC) tumor cell growth. As in PDAC, we found upregulated RalA and RalB activation in CRC tumor cell lines and tumors. Surprisingly we found antagonistic roles for RalA and RalB in the regulation of CRC tumor cell anchorage-independent growth. This observation contrasts with PDAC, where RalA but not RalB is necessary for PDAC tumor cell anchorage-independent growth. Our results emphasize cancer cell type differences in Ral function and hence the need for distinct Ral targeted therapeutic approaches in the treatment of CRC vs. PDAC.